A Pemberdayaan Masyarakat Melalui Penyuluhan Cegah Balita Bawah Garis Merah dengan Perawatan Tepat oleh Ayah dan Ibu di RW 01 dan 02 Kelurahan Kampung Jua Nan XX: Prevention of Under-Five Underweight through Parent Empowerment and Family Support in Kampung Jua Nan XX Village, Padang City - Desmawati Desmawati; Erwani Erwani; Nurjanah Nurjanah; Shinta Maya Sari; Yulia Afwinda Saputri (BULETIN ILMIAH NAGARI MEMBANGUN, 2026)
This community service initiative was carried out to address the persistent issue of underweight or Bawah Garis Merah (BGM) among children under five through a family-centered empowerment approach in Kampung Jua Nan XX Village. The program aimed to strengthen parental capacity in recognizing, preventing, and managing early signs of growth faltering. A participatory method was employed, integrating health education sessions with home visits for families of BGM toddlers. The intervention involved 30 parents and focused on interactive counseling, distribution of educational materials, and growth monitoring. Pre- and post-tests were used to measure improvements in parental knowledge, while anthropometric assessments were conducted for four toddlers identified as BGM and receiving supplementary feeding. The results demonstrated a notable increase in parental understanding of nutrition and growth monitoring, with total correct responses rising from 35 to 58 after the intervention. Among the four toddlers monitored, two showed meaningful improvements in nutritional status following 57 days of supplementary feeding and family support, while the remaining two exhibited minimal changes influenced by irregular health service utilization and limited household resources. These findings highlight that preventing BGM requires a comprehensive strategy that goes beyond food-based interventions and actively involves both parents, particularly in strengthening caregiving practices and increasing health service engagement. The study concludes that family empowerment combined with regular monitoring and contextualized support can serve as an effective model for addressing early childhood undernutrition in community settings.